ESL LEARNERS’ SECOND LANGUAGE ANXIETY AND MOTIVATION TO LEARN ENGLISH AT UNIVERSITY LEVEL IN LAHORE - Sumayya Kainat; Dr. Shahid Hussain Shahid; Aleena Khan; Asmara Batool (International Journal of Contemporary Issues in Social Sciences, 2023)
Learning a second language has diverse opportunities and multiple challenges, and forbearance of these variables yields productive outcomes for the learners. Many studies have been conducted, but more needs to be done to alleviate the anxiety experienced by learners of English as a Second Language. The current study collected data from university students to assess the effects of anxiety and motivation on learners’ learning attitudes at university level. We employed FLCAS and MAQ for the collection of data from a sample size of 150 students at the English department of the University of Lahore. The researchers analyzed the relationship between anxiety and motivation by using the Pearson correlation coefficient. Statistical methods were used to investigate 1) the anxiety level among university students, 2) the motivation level of ESL learners, and 3) the link between anxiety and motivation in learning English as a second language. The results of the investigation found that the dominant part of the participants felt higher levels of language anxiety as ESL learners. Second, it was also observed that students in a classroom experience a moderate level of motivation. Third, the Pearson Correlation Coefficient shows that there is a significant link between motivation and anxiety. It is proposed that the anxiety level of students can be reduced by a conducive learning atmosphere and a variety of teaching approaches. The motivation of ESL learners can be increased and anxiety can be alleviated by careful handling and up-to-date pedagogical skills like pedocentric approaches that avoid putting the students’ ego at stake.